1969
DOI: 10.1021/jf60164a047
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory isolation and identification of a metabolite of carbaryl in urine and milk

Abstract: This study confirms the chemical nature of the major organic extractable metabolite of carbaryl in milk and urine. The data obtained with the aid of ultraviolet, infrared, mass, and nuclear magnetic resonance spectroscopy are consistent with the structure of the methylcarbamate of 5,6-dihydro-5,6dihydroxy-1-naphthol. The compound exhibits a lower degree of toxicological hazard than carbaryl, as evidenced by anticholinesterase and fly bioassay tests, and has a very low potential as a microbial mutagenic agent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…Mass measurements made when the spectra were determined were in agreement with theoretical for dihydro-dihydroxycarbaryl (mje 235), a dihydro-dihydroxynaphthol (mje 178), and a dihydroxy-naphthalene (mje 160). These results are in agreement with those reported by Baron et al (1969) on a carbaryl metabolite isolated from cow urine and milk. The samples remaining after the initial analysis were dissolved in absolute ethanol and acidified with one drop of concentrated HC1 and allowed to stand for 3 hr.…”
Section: Resultssupporting
confidence: 93%
“…Mass measurements made when the spectra were determined were in agreement with theoretical for dihydro-dihydroxycarbaryl (mje 235), a dihydro-dihydroxynaphthol (mje 178), and a dihydroxy-naphthalene (mje 160). These results are in agreement with those reported by Baron et al (1969) on a carbaryl metabolite isolated from cow urine and milk. The samples remaining after the initial analysis were dissolved in absolute ethanol and acidified with one drop of concentrated HC1 and allowed to stand for 3 hr.…”
Section: Resultssupporting
confidence: 93%
“…Bands were eluted with acetone and analyzed by mass spectrometric and infrared spectrophotometric techniques. Details of the techniques were previously reported (Baron et al, 1969).…”
mentioning
confidence: 99%
“…Accurate mass measurement of the M-Cl fragment group (m/ e 359) led to a probable empirical formula for the compound of C12HsCla02' On the basis of this information, it was suggested that the fecal metabolite was a monohydroxy derivative of dieldrin substituted in position 4a or 5. BARON et al (1969), in the course of a study involving the occurrence of metabolites of carbaryl in the milk and urine of the dairy cow, presented confirmatory spectroscopic data which identified a major metabolite as the methyl carbamate of 5,6-dihydro-5,6-dihy-droxy-1-naphthol. In this study data from low and high resolution mass analysis, field ionization studies, low voltage mass spectra and the mass spectra of model compounds were utilized in addition to infrared and nuclear magnetic resonance studies _ to establish the structure of the metabolite.…”
Section: A) Animal Metabolism Of Pesticidesmentioning
confidence: 91%